Transforming the global plastics economy: The political economy and governance of plastics production and pollution - Diana Barrowclough; Carolyn Deere Birkbeck (University of Oxford, Global Economic Governance Programme (GEG), 2020)
Despite growing alarm about plastic pollution, the production and use of plastics is forecast to continue to expand over coming decades. Efforts on the part of governments, civil society and business to reduce plastics pollution are encouraging signs of awareness and an appetite for engagement but are, nonetheless, failing to stem the tide of growing plastic production, use and waste. To date, there has been remarkably little scholarly interest in the global plastics economy. Both the global political economy and root causes of the plastics crisis are vastly under-studied. Most efforts towards change (whether voluntary or regulatory) have been focused on the 'end of life' of the plastics value chain, rather than its starting point. Attention to the upstream dimensions of the plastics economy - that is, to the production end of the plastics life cycle - is not yet central to international policy discussions nor are the international policy frameworks needed to address them. This paper seeks to spur discussion on an integrated set of policies - and an enabling international framework - to support an effective transformation of the plastics economy, including a just and sustainable transition, away from excessive plastic production and unnecessary use. It brings together, for the first time in the literature, a first step toward an integrated analysis of what we call the missing 'political economy piece' of evolving global discussions of challenges and responses to plastic pollution. It highlights some critical policy steps that can be taken to help face these structural challenges and transform our economy away from the grip of plastics, along with a policy-oriented research agenda.
Keywords: 330; Kunststoffindustrie; Umweltbelastung; Kunststoffverpackung; Strukturwandel; Ökologische Verpackung